Dry Eye Syndrome Due to Botulinum Toxin Type-A Injection: Guideline for Prevention - Ozgur, Omar (University Clinical, Education & Research Associate (UCERA), 2012)
Dry eye syndrome is a potential complication of botulinum toxin type-A injection (BTX-A) into the lateral canthal rhytids (crow's feet). The early manifestations of this syndrome are subtle and are rarely reported to the treating physician. A guideline for early detection of dry-eye state is proposed, in order to avoid more troublesome adverse effects that may develop with repeated injections of BTX-A into the crow's feet region. If suspected early, clinical manifestations remain minor and are reversible. However, delayed diagnosis may lead to troublesome and persistent symptoms. A novel and practical grading scale of lower eyelid snap-back and distraction tests is offered that helps in documenting patient's clinical progress and in deciding when BTX-A injections should be delayed or discontinued.